Management of Hereditary Breast and Ovarian Cancer. The Asian Experience - Ava Kwong (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
BRCA1/BRCA2 mutations are the most common high penetrant genes associated with an increased lifetime risk for hereditary breast and ovarian cancer (HBOC). Although genetic testing is standard of care in Western developed countries, there are still variations in availability of genetic testing and risk assessment for HBOC in Asia. Depending on the countries, there are variations in the clinical strategies and cancer management. The Asian BRCA Consortium has grouped together 14 Asian countries and reviewed genetic counselling/testing uptake rates and clinical management options in these countries. Moreover economic factors, healthcare and legal frameworks, and cultural issues affecting the genetic service availability in Asia were discussed. Mutation spectrum, and VUS rates and the increase use of NGS gene panel testing poses more decisional issues in the clinical management of Hereditary Breast cancer in Asia. These will be discussed.Keywords: BRCA1/BRCA2, germline, HBOC, Asia BRCA Consortium, NGS